Synthesis And Characterisation Of Halloysite Nanotubes Supported Nickel Catalysts For Hydrogenation Of Benzene - Yusli, Farhana (2017)
Two series of halloysite nanotubes supported nickel catalysts (Ni-HNT) were prepared using classical and non-classical methods via impregnation technique. The Ni content was varied between 2-14 wt% in both series of Ni-HNT catalysts. Catalysts were characterized via Atomic Absorption Spectroscopy (AAS), Scanning Electron Microscope (SEM), N2-adsorption desorption analysis, X-ray Diffraction (XRD), High Resolution Transmission Electron Microscope (HRTEM), Hydrogen Temperature-Programmed Desorption (H2-TPD), Hydrogen Chemisorption and Hydrogen Temperature-Programmed Reduction (H2-TPR) techniques.